Sosialisasi Pengukuran Tingkat Kematangan (Maturitas) Science Techno Park Menuju Level Utama Nasional bagi Akademisi - Prima Fithri; Hanalde Andre; Uyung Gatot Syafrawi Dinata; Eka Candra Lina; Cesar Welya Refdi; Wenny Surya Murtius (Warta Pengabdian Andalas, 2023)
Applying science and technology encourages innovation, increasing development productivity, independence and national competitiveness. Indonesia has a science and technology area named Science Techno Park (STP). Maturity measurement is an indicator of the level of an STP to apply science and technology for the welfare of society. There are three levels of maturity for STP, which are low (pratama), middle (madya), and high (utama). Before entering the best maturity level, STP must go through various kinds of preparation and fulfil the elements contained in it. The community service activity team at Universitas Andalas conducted a web seminar (webinar) to socialise the maturity assessment for STP Unand from the academic side. The webinar invited two experts on STP maturity measurement. One of the primary assessments is the number of products produced that are expected to come from the results of academic research. This activity can help STP Unand prepare to increase its maturity to a high level.